O reflexo estético como reflexo da realidade: a particularidade em Diego Rivera - Camargo, Marcia Helena Domingues [UNESP] (2015)
This work aims to analyze the particularity of aesthetic reflection of Diego Rivera murals. For that we use the categories of dialetics developed by Georg Lukács. Rivera created a whole iconography within the Mexican mural painting to express the past, the present and what would be the future for Mexico. In a original way Rivera synthesized the particular situation of Mexico, within the grounds in the Marxist concept of class struggle. We performed a literature search and we analysis pictures of Diego Rivera's works. It is understood with this study that both the aesthetic reflection as scientific reflection are forms of analysis and understanding of objective reality. Finally, we understand that the Rivera murals deal is a high art within the Lukascian concept, that is, it enables men to increase their condition in-itself, everyday life, to a relationship for-itself, generic.